2018
DOI: 10.21307/jofnem-2018-026
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Re-Description and 18 S rDNA Sequence Confirmation of the Pinworm Aspiculuris tetraptera (Nematoda, Heteroxynematidae) Infecting the Laboratory Mice Mus musculus

Abstract: Aspiculuris tetraptera is a heteroxynematid nematoda infecting most of the laboratory animals, occasionally mice which represent the mostly used animal for biological, medical, and pharmacological studies. The present study aimed to investigate the prevalence of nematode parasites infection in the laboratory mice Mus musculus in Egypt. Morphologically, this oxyurid possessed four distinct cephalic papillae on a cephalic plate, with three small rudimental lips carrying two sessile poorly developed labial papill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 74 publications
(54 reference statements)
4
7
0
Order By: Relevance
“…It has been reported that infections with the rodents’ oxyurid nematodes; A. tetraptera and S. obvelata generally influenced by the age of the host and infection with the first worm affect older animals while the latter affects younger animals and occurs in young mice [ 42 , 43 ]. Reporting of high prevalence in our study and Abdel-Gaber et al [ 37 ] study may be explained by the fact that adult mice were investigated in both studies as has been reported before [ 42 , 43 ].…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…It has been reported that infections with the rodents’ oxyurid nematodes; A. tetraptera and S. obvelata generally influenced by the age of the host and infection with the first worm affect older animals while the latter affects younger animals and occurs in young mice [ 42 , 43 ]. Reporting of high prevalence in our study and Abdel-Gaber et al [ 37 ] study may be explained by the fact that adult mice were investigated in both studies as has been reported before [ 42 , 43 ].…”
Section: Discussionsupporting
confidence: 70%
“…Morphological as well as morphometric characteristics showed that the species recovered from mice autopsied at the Department of Zoology, College of Science, King Saud University, resembles A. tetraptera as has been described previously by [6,36]. There were slight morphometric differences between other A. tetraptera described from other studies [37].…”
supporting
confidence: 77%
See 2 more Smart Citations
“…However, articles that were ambiguous regarding their relevance by their title and abstract were subjected to full-text analysis. Only documents published in English were considered for the review [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ,…”
Section: Methodsmentioning
confidence: 99%